2016
DOI: 10.1111/hepr.12829
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of transient elastography in Japanese patients with non‐alcoholic fatty liver disease

Abstract: In NAFLD patients, TE has excellent utility for the assessment of liver fibrosis, particularly for advanced stage cases. The cut-off value of LSM by TE for predicting liver fibrosis stage ≥3 is 10.0 kPa in Japanese NAFLD patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 36 publications
(42 reference statements)
1
10
0
Order By: Relevance
“…Since then, many reports have been published and recently, Seki et al . reported that the cut‐off value of LSM by VCTE for predicting liver fibrosis stage ≥3 is 10.0 kPa in Japanese NAFLD patients . Furthermore, we previously reported the 4‐year disease progression in NAFLD patients as evaluated using LSM data obtained using VCTE …”
Section: Discussionmentioning
confidence: 54%
“…Since then, many reports have been published and recently, Seki et al . reported that the cut‐off value of LSM by VCTE for predicting liver fibrosis stage ≥3 is 10.0 kPa in Japanese NAFLD patients . Furthermore, we previously reported the 4‐year disease progression in NAFLD patients as evaluated using LSM data obtained using VCTE …”
Section: Discussionmentioning
confidence: 54%
“…Fourth, the diagnostic accuracy of T4C7S CLEIA should be compared with the LSM using elastography 30 . Our previous studies revealed that the AUROCs of the T4C7S RIA and LSM of vibration‐controlled transient elastography (FibroScan®) for predicting the advanced liver fibrosis were comparable 13,31 . Fifth, a significant increase in the serum level of T4C7S was observed with increasing severity of lobular inflammation and hepatocyte ballooning in this study.…”
Section: Discussionmentioning
confidence: 60%
“…They found that CAP and LSM by FibroScan to assess liver steatosis and fibrosis with AUROC values ranged from 0.70 to 0.89 [ 84 ]; however, VCTE was less accurate in distinguishing a lower fibrosis stage, higher steatosis grades, or the presence of NASH [ 103 ]. In a few Japanese studies, 9.6–10.8 kPa of LSM was an optimal cutoff value for identifying advanced fibrosis in NAFLD [ 104 , 105 , 106 ].…”
Section: Noninvasive Tests For Diagnosis Of Nafld and Staging Fibrmentioning
confidence: 99%
“…VCTE is recommended as the second step, considering its simplicity, portability, and non-invasiveness. In a few Japanese studies, 9.6–10.8 kPa of LSM was an optimal cutoff value for identifying advanced fibrosis in NAFLD [ 104 , 105 , 106 ]. A two-step referral pathway system from Canada suggested that the cutoff value of VCTE was 8.0 kPa after triaging by FIB-4 index [ 111 ].…”
Section: Two-step Algorithm In Nafld Diagnosismentioning
confidence: 99%